2012
DOI: 10.1111/j.1600-0536.2011.02004_3.x
|View full text |Cite
|
Sign up to set email alerts
|

The critical review of methodologies and approaches to assess the inherent skin sensitization potential (skin allergies) of chemicals Part II

Abstract: To identify specific cases, classes or specific use situations of chemicals for which 'safety thresholds' or 'safety limits' were set (in regulations, standards, in scientific research/clinical work, etc.) and critically review the scientific and methodological parameters used to set those limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 157 publications
(196 reference statements)
0
12
0
Order By: Relevance
“…ROAT data can contribute valuable information in the risk assessment process, especially when risk assessments based on sensitization testing have failed to predict the true risk of a hapten, as in the case of the preservative MDBGN and now also MI. Previous risk assessments conducted in Europe and the U.S.A., based on sensitization data, severely underestimated the allergy risk from preserving cosmetic products with MI .…”
Section: Discussionmentioning
confidence: 99%
“…ROAT data can contribute valuable information in the risk assessment process, especially when risk assessments based on sensitization testing have failed to predict the true risk of a hapten, as in the case of the preservative MDBGN and now also MI. Previous risk assessments conducted in Europe and the U.S.A., based on sensitization data, severely underestimated the allergy risk from preserving cosmetic products with MI .…”
Section: Discussionmentioning
confidence: 99%
“…Isothiazolinones are well known for causing skin allergy. These preservatives/biocides include methylchloroisothiazolinone (MCI) and methylisothiazolinone (MI), widely used in occupational, household and cosmetic products, and benzisothiazolinone used in paints, varnishes and adhesives . An epidemic of contact allergy to the mixture MCI/MI was observed in the mid 1990s but significantly decreased after European Cosmetics regulation .…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of coding we treated them as cosmetics fragrances which could have been contained in detergents or cleaning products. The increase of OACD associated with cosmetics and probably fragrances in personal services activities (composed almost exclusively of hairdressers) and in HSW is consistent with an increase in the use of fragranced products such as detergents, which may not be under the control of the 1976 EU Cosmetics Directive . This directive is mainly written for the protection of consumers but different types of use of these products not covered by the regulation may occur in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of allergic contact dermatitis is made on the basis of a positive patch test result and the ascertained exposure to the contact allergen in question in a way that fully or partly explains the dermatitis (7). Systematic studies of quantitative exposure assessment of contact dermatitis, supported by experimental dose-response studies on sensitized individuals, support this definition of allergic contact dermatitis (9)(10)(11)(12). Moreover, experimental studies have found that real-life repeated allergen exposures can elicit allergic contact dermatitis.…”
mentioning
confidence: 99%